2014
DOI: 10.21608/jhiph.2014.20336
|View full text |Cite
|
Sign up to set email alerts
|

Ventilator Associated Pneumonia: Incidence and Risk Factors in a University Hospital

Abstract: Background: Ventilator associated pneumonia (VAP) is a type of nosocomial pneumonia associated with increased morbidity and mortality. Awareness about the risk factors can be used to implement simple and effective preventive measures. Objectives: To determine the factors associated with development of VAP and its microbial profile among patients admitted to ICUs. Methods: A nested case-cohort study was conducted at Al-Hussein university hospital in Cairo city, Egypt for a period of 6 months from the 1 st of Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…In the current study finding, corticosteroid use was significantly associated with the development of VAP. This is similar to findings of studies conducted in Al-Azhar University, Egypt (95% CI: 1.1–9.2) 22 and India (p-value: 0.013) 31 but it was not in studies conducted in India (95% CI: 0.41–2.78) 24 , 26 and Turkey (95% CI: 0.75–1.60). 28 The reason for these differences might be due to differences in the methods of data analysis; logistic analysis was used in Indian and Turkey studies while the log binomial method of analysis was executed in this study.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In the current study finding, corticosteroid use was significantly associated with the development of VAP. This is similar to findings of studies conducted in Al-Azhar University, Egypt (95% CI: 1.1–9.2) 22 and India (p-value: 0.013) 31 but it was not in studies conducted in India (95% CI: 0.41–2.78) 24 , 26 and Turkey (95% CI: 0.75–1.60). 28 The reason for these differences might be due to differences in the methods of data analysis; logistic analysis was used in Indian and Turkey studies while the log binomial method of analysis was executed in this study.…”
Section: Discussionsupporting
confidence: 85%
“…This study found that the cumulative incidence of VAP was 27.9% (95% CI: 23%−33%) and the incidence rate was 45.7 per 1000 ventilator days, It agrees with studies from Istanbul 28%, 7 and in India 27.71%, 21 but is lower than a study conducted in Egypt, 57.5%. 22 This may be due to sociodemographic variation, and small sample size in the Egyptian study. In studies conducted in Canada and India, the incidence of VAP was 17.5% 23 and 18% 24 respectively, which were lower than this study's findings.…”
Section: Discussionmentioning
confidence: 94%